1981
DOI: 10.1038/289751a0
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation in the control of expression of bacterial operons

Abstract: Bacterial operons concerned with the biosynthesis of amino acids are often controlled by a process of attenuation. The translation product of the initial segment of the transcript of each operon is a peptide rich in the amino acid that the particular operon controls. If the amino acid is in short supply translation is stalled at the relevant codons of the transcript long enough for the succeeding segment of the transcript to form secondary structures that allow the transcribing RNA polymerase molecule to proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
430
3
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 733 publications
(444 citation statements)
references
References 74 publications
10
430
3
1
Order By: Relevance
“…It has been shown that in some cases rare codons can slow elongation rates along an mRNA and cause ribosomal pausing (4,8,33,38,42). Moreover, nonuniform translation rates along individual mRNAs have been implicated as being important in a number of cellular processes, including protein secretion, frameshifting, transcriptional attenuation, and protein folding (2,4,11,39,43). Indeed, it has been postulated that ribosomal pausing may be involved in the decay of other mRNAs (6,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in some cases rare codons can slow elongation rates along an mRNA and cause ribosomal pausing (4,8,33,38,42). Moreover, nonuniform translation rates along individual mRNAs have been implicated as being important in a number of cellular processes, including protein secretion, frameshifting, transcriptional attenuation, and protein folding (2,4,11,39,43). Indeed, it has been postulated that ribosomal pausing may be involved in the decay of other mRNAs (6,13).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous possible mechanisms by which a putative ribosomal pause could stimulate mRNA turnover mediated by the MIE. For instance, a ribosome stalled at a particular site might affect RNA folding (43) and promote formation of a structure that is recognized as a signal for decay. Alternatively, a pause in translational elongation might permit sequences 3' of the pause to be relatively ribosome free.…”
Section: Discussionmentioning
confidence: 99%
“…However, this inhibition is ''leaky'': there is some transcription of the operon even in the presence of tryptophan; this would waste energy for producing enzymes that are not needed. A second regulatory mechanism, called attenuation, knocks down this residual transcription on the trp operon [2,3].…”
Section: The Experimentsmentioning
confidence: 99%
“…17 The leader transcript refers to the 162 nt long untranslated region (UTR) preceding the structural genes. 10 Along this leader transcript, the ribosomal binding site resides at the 5' end, 18 and an internal transcription termination signal is located distally before the first structural gene E. 10,19 This termination signal, lying within the attenuator, can be recognised by RNA polymerase to produce a transcript of about 140 nt (137-141) length. 9.20 This shorter transcript generates a leader peptide consisting of 14 residues whose distal end has a tandem of trp residues.…”
Section: Trp Operon Leadermentioning
confidence: 99%
“…9.20 This shorter transcript generates a leader peptide consisting of 14 residues whose distal end has a tandem of trp residues. 10 This leader peptide is involved in the attenuation regulatory strategy where the Trp operon leader is utilised for adaptation to the metabolic condition concerning the biosynthesis of trp. 9 Attenuation in Tryptophan operon leader The trp-activated repressor protein (trpR) is stimulated upon trp binding to compete against RNA polymerase, 21 and consequently switches off the initiation of trp operon transcription.…”
Section: Trp Operon Leadermentioning
confidence: 99%